O ensino do português: pedagogía e pedagogismo - Cerejeira, Manuel (2006)
This essay is a brief exposition of the transformations that affected the teaching of Portuguese in the second half of the twentieth century. I examine how the pedagogical and didactic changes mainly result from the evolution of linguistic studies. Moreover, I explain why it is essential to promote a serious and well-founded pedagogical and didactic reflection on the teaching of Portuguese in order to prevent sterile and harmful pedagogisms.